Perceived Satisfaction of Landscape Condition: An Empirical Investigation in Majlis Bandaraya Kuala Terengganu (MBKT) - Wan Hariff Rafany, Wan Muda (2011)
Malaysia is seriously embarking on its beautification programme. Landscaping condition are being emphasized especially in the Local Authorities areas.As more new towns and urban areas are developed and more money is spent on landscapes,the need to find a mechanism that responds to these issues is becoming urgent This paper highlights the perceived satisfaction on landscape condition in a local government agency in Peninsular Malaysia.The aim of this study is as a reference for local authotities to manage their landscape condition base on public response towards their satisfaction.There were 169 involved in the survey.The data was analyze using Statistical Package for Social Science (SPSS) Ver 17.0.The findings of the research confirm that quality success driver have a significant relationship with perceived satisfaction on facilities and maintenance of landscape condition.The relations of perceived satisfaction on landscape condition for all level of incomes and educations did't show any differences. Moreover,the results show that the awareness on the facilities and maintenance of landscape condition can be enhanced through proper and structured programme to all residents.